Analysis of the mechanical properties and wear characteristics of nail teeth based on sowing layer residual film recovery machine. (January 2023) - Su, Zipeng; Li, Jingbin; Zhang, Zhiyuan; Ren, Sixue; Shi, Yameng; Wang, Xianfei
Highlights: The wear characteristics of three commonly used nail teeth materials in soil and rubber environments were studied. The mechanical properties of three types of nail teeth specimens were studied. The fracture mode of the nail tooth specimen was analyzed. The wear mechanism of nail tooth specimens under the interaction of soil and rubber was studied. Abstract: This study aims to address the problem of the arc-shaped nail tooth, a key component in pre-sowing film recovery machines, being prone to wear and fracture deformation. To determine its wear and damage mechanism, this paper uses chlorinated butyl rubber and soil particles to simulate the wear environment of the nail tooth. Carbon structural steel (45 steel), spring steel (60Si2 Mn), and alloy structural steel (40Cr) are selected for performing friction wear tests and mechanical property analysis. Detailed failure analysis is performed using scanning electron microscopy (SEM), three-dimensional (3D) morphology, and energy-dispersive X-ray spectroscopy (EDS). The results demonstrate that abrasive wear occurred in all samples. #45 steel and 40Cr showed significant plastic spalling during the wear process. 60Si2 Mn has the lowest surface roughness and wear depth at 0.5709 and 2.412 µm, respectively. By combining the micromorphological characterization and element content changes of these samples after wear, the results demonstrate that the wear and oxidation of 40Cr and #45 steel are more severe than 60Si2 Mn. "River-pattern" fracture and tear ridges were observed in the 40Cr fracture surface, indicating quasi-cleavage fracture characteristics. 60Si2 Mn exhibits multiple ductile dimples, an apparent ductile fracture mechanism; moreover, #45 steel exhibits good plasticity with no observed fracture. Based on comprehensive analysis, 60Si2 Mn has excellent wear and plastic deformation resistance. This study provides a reference for selecting the material for the film-picking nail teeth in mulching film recycling machines.